Collective Variable for Metadynamics Derived From AlphaFold Output - Spiwok, Vojtěch; Kurečka, Martin; Křenek, Aleš (Frontiers in Molecular Biosciences, 2022)
AlphaFold is a neural network-based tool for the prediction of 3D structures of protein. In CASP14, a blind structure prediction challenge, it performed significantly better than other competitors, making it the best available structure prediction tool. One of the outputs of AlphaFold is the probability profile of residue-residue distances. This makes it possible to score any conformation of the studied protein to express its compliance with the AlphaFold model. Here we show how this score can be used to drive protein folding simulation by metadynamics and parallel tempering metadynamics. Using parallel tempering metadynamics, we simulated the folding of a mini-protein Trp-cage and beta hairpin and predicted their folding equilibria. We see the potential of the AlphaFold-based collective variable in applications beyond structure prediction, such as in structure refinement or prediction of the outcome of a mutation.